1986
DOI: 10.1148/radiology.159.3.3010375
|View full text |Cite
|
Sign up to set email alerts
|

Uterine neoplasms: MR imaging.

Abstract: Magnetic resonance (MR) studies were performed on 20 healthy volunteers and 41 patients with proved cervical and uterine neoplasms. MR imaging demonstrated normal uterine landmarks in all patients. On T2-weighted images, the normal uterine wall could be differentiated into three distinct layers: a central high-intensity zone, a junctional low-intensity band, and a peripheral medium-intensity area. While most of the normal cervices had only two distinct zones (central high-intensity zone and peripheral low-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…The cervix typically has a high-signal central zone from the endocervical canal with surrounding low signal intensity from the fibrous stroma of the uterus. An additional layer of intermediate signal intensity more peripherally also has been seen in some patients [4] (Fig. 1C).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The cervix typically has a high-signal central zone from the endocervical canal with surrounding low signal intensity from the fibrous stroma of the uterus. An additional layer of intermediate signal intensity more peripherally also has been seen in some patients [4] (Fig. 1C).…”
Section: Discussionsupporting
confidence: 55%
“…The delineation of various anatomic layers within the uterus and cervix has been noted on 12-weighted, SE sequences [4,7,8]. In the uterine body, three layers of different signal intensity can be identified (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such patients, MRI may be useful for detection of intrauterine lesions. MRI is becoming an accepted and useful modality for the evalua tion of endometrial carcinoma as it provides direct tumor visualization and offers more accurate clinical staging compared with other imaging modalities, and contrastenhanced MR images with Gd-DTPA improve both tu mor detection and assessment of the depth of myometrial invasion [2][3][4], However, there is no report of contrastenhanced MR images with Gd-DTPA for detection of car cinosarcoma [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical usefulness of magnetic resonance imaging (MRI) in the evaluation of endometrial carcinoma has been reported [2][3][4]. However, there are few reports of MRI for the diag nosis of carcinosarcoma, and the specific MRI findings of this tumor have not been reported [5,6], In the present report, we describe the MRI findings in a patient with car cinosarcoma.…”
Section: Introductionmentioning
confidence: 81%